PROTOTIP SUMBER ENERGI CADANGAN DI BASE TRANSCEIVER STATION (BTS) - Huda, Nurul; Adam, Ahamd Antares; Dodu, A.Y. Erwin (MEKTRIK)
Electrical energy until the current is still very important role in meeting the daily needs of both the household, industrial enterprises, social activities and others. Electrical energy consumption is increasing from year to year, according to the development of the load with increasing electricity consumers because bayaknya construction of private homes, office buildings, large and small companies, resulting in power generation has increased considerable expense, this resulted in a power outage by the PLN. From the test results Prototypes Energy Resources Reserves in Base Transceiver Station (BTS), it can be concluded as follows: That the converter can work well with generating keluaran18 volts DC. Measurement results can be seen that the power generated by this converter is equal to 35 kWatt and the length of time the back-up battery is for 11.67 hours That pattern converter and battery installation is a pattern.